PENYULUHAN PENGGUNAAN ANTIBIOTIK RASIONAL PADA LANSIA DI PUSKESMAS PUUWATU SEBAGAI UPAYA PENCEGAHAN RESISTENSI ANTIBIOTIK - Rachma Malina; Yamin; Sri Rahmaniar; Athiyah Syifa Aziz; Gizma Sasikirana Syahrani; Nur Azizah; Yepsan B. Manguntu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Irrational use of antibiotics is one of the main factors contributing to the increasing prevalence of antibiotic resistance. Older adults are at a higher risk of medication misuse due to age-related declines in physical and cognitive functions. This community service activity aimed to improve older adults' knowledge regarding the rational use of antibiotics. The program was conducted on May 23, 2026, at UPTD Puuwatu Community Health Center, Kendari City, using the Interactive Health Edu-Counselling method. Educational materials were delivered through presentations and leaflets, complemented by interactive discussions. The results indicated an improvement in participants’ understanding of appropriate antibiotic use, the importance of completing prescribed antibiotic courses, and the risks associated with using antibiotics without a prescription. The activity was successfully implemented with the active participation of 27 older adults. This educational program contributed to increasing community awareness of rational antibiotic use as an effort to prevent antibiotic resistance.